Effectiveness of cycle cross-training between competitive seasons in female distance runners - White, L. J.; Dressendorfer, R. H.; Muller, S. M. (The Journal of Strength and Conditioning Research, 2003)
The purpose of this study was to examine whether substituting 50% of run training volume with cycling ("cross-training") would maintain 3,000-m race time and estimated O2max in competitive female distance runners during a 5-week recuperative phase. Eleven collegiate runners were randomly assigned to either the run training-only (R) group (n = 6) or the cycle training (R/C) group (n = 5), which cross-trained on alternate days. The groups trained daily at a reduced intensity (75-80% of maximum heart rate). Training volume was similar to the competitive season (40-50 mi·wk1) except that cycling represented 50% of volume for the R/C group. On follow-up, 3,000-m time was 1.4% (9 seconds) slower in the R group and 3.4% (22 seconds) slower in the R/C group. No important change in estimated O2max was found for either group. It was concluded that cycle cross-training adequately maintained aerobic performance during the recuperative phase between the cross-country and track seasons, comparable to the primary sport of running.